IMPLEMENTASI DIGITALISASI EWS DAN MEWS: KELENGKAPAN DATA DAN KESESUAIAN ESKALASI DI RUANG ALAMANDA RSUP DR. HASAN SADIKIN TAHUN 2022 - Widianti Kuswara, Sani; Darmareja, Rycco (Jurnal Kesehatan An-Nuur, 2025)
Maternal mortality and morbidity in hospitals mostly occur in preventable cases. The early warning system, as one of the prevention efforts based on clinical findings, has not been implemented comprehensively. The large number of incomplete data and the inconsistency of the early warning system escalation are the basis for the development of electronic technology solutions. With an electronic system, it is expected that management can be carried out earlier, preventing life-threatening conditions because patients will be treated faster so that the expected output is better. Objective: This study aims to analyze the differences in the completeness of data entry and the appropriateness of the early warning system escalation before and after the digitalization of EWS and MEWS in the Alamanda Room of Dr. Hasan Sadikin Hospital, Bandung. Method: This study is a quantitative study using a pre-experimental design with a one-group pre-post test approach. The sampling technique with a total sampling of 648 datas, both before and after digitalization. Secondary data was taken from all data from the results of the filling responses that had been collected. Data analysis used univariate frequency distribution analysis and bivariate analysis using the Chi-Square and Fisher's Exact tests. Results: Based on the results of the study, it was found that according to the hospital's Standard Operating Procedure, the completeness of EWS data filling after the intervention increased to 97.2%, the appropriate EWS data escalation after the intervention became 56.61%. MEWS data also increased after the intervention to 91.2%, the appropriate MEWS data escalation after the intervention became 63.6%. The results of the bivariate data analysis showed a significant difference in the completeness of data filling and the appropriateness of escalation before and after digitalization with a p-value of 0.000. Conclusion: Digitalization can improve the completeness of data filling based on SOP and the appropriateness of the hospital's early warning system escalation. The appropriateness of escalation and rapid clinical response has an impact on the quality of maternal care, patient safety, and the quality of hospital services.